Cave of Bones [large type] : a Leaphorn, Chee and Manuelito Novel / Anne Hillerman. - Hillerman, Anne, 1949- (Hillerman, Tony, Leaphorn and Chee novel., 2018)
Annie, a young participant on a solo experience, has just returned and is traumatized. Gently questioning the girl, Tribal Police Officer Bernadette Manuelito learns that Annie stumbled upon a human skeleton on her trek. While everyone is relieved that Annie is back, they're concerned about an instructor who went out into the wilds of the rugged lava wilderness to find the missing girl. The instructor vanished somewhere in the volcanic landscape known as El Malpais. Solving the twin mysteries will expose Bernie to the chilling face of human evil.